A framework for reducing turnover intention among police personnel in Abu Dhabi - Aldarmaki, Obaid (2021)
Turnover intention is a universal issue that faces countries and organizations. The rate of turnover is higher in United Arab Emirates (UAE) compared with regional countries and the global average. Moreover, prior literature focused on the turnover intention in the private sector in developed countries. In the UAE public sector, the rate of turnover intention is higher than in the private sector. Among the public sector, the highest percentage of turnover is among the police personnel. Accordingly, the purpose of this study is to propose a framework for turnover among police personnel. The literature was reviewed to understand the findings of previous studies and identify significant turnover predictors. Moreover, the leadership theories, social exchange theory and organizational justice were reviewed. Based on the review, this study proposed that leadership style and organizational justice will affect negatively the turnover intention. The study also proposed that the quality of working life will mediate the effect of leadership style and organizational justice on turnover intention. These causal relationships would be also moderated by trust in the supervisor. The population of this study is police personnel in Abu Dhabi. Using stratified sampling, the study collected the data from 388 police personnel using questionnaires. The data were analysed using both Statistical Package for Social Science (SPSS) and Structural Equation Modelling Partial Least Square (SEM-PLS). The findings indicated that the organizational justice and leadership style affected significantly the turnover intention. Quality of working life mediated the effect of leadership style on turnover intention while trust in supervisor moderated the relationship between leadership style and turnover intention. Having these variables satisfied will lead to high job satisfaction, motivation, happiness, job security, and organizational commitment which in turn will lead to turnover prevention and better productivity. In conclusion, decision-makers in Police Headquarter have to focus on the implications of organizational justice and leadership style as well as income equality and training and development for turnover intention prevention.